Perianal herpetic ulcers in immunosuppressed patients. Report of two cases - María Lorena Re Domínguez; Evelín Magalí Cuevas Jara; Guadalupe Barboza; Beatriz Di Martino Ortiz; Mirtha Rodríguez Masi; Oilda Knopfelmacher Domínguez; Lourdes Bolla de Lezcano (Our Dermatology Online, 2017)
Genital herpes is the most common cause of ulcers in sexually transmitted diseases (STDs). It is presented as a single or multiple, painful injury, accompanied by bilateral, also painful, lymphadenopathy. In immunocompromised patients, such as those affected by HIV, Herpes Simplex Virus (HSV) infections have a variety of clinical manifestations; they may be located, scattered or atypical. In addition, lesions may be more extensive and persistent than HIV-negative patients. We present two cases of immunocompromised patients with perianal herpetic ulcers, one HIV carrier, and the other with leukopenia caused by visceral Leishmaniasis.